Hubungan Komunikasi Interpersonal Dalam Keluarga Dengan Perkembangan Moral Anak Di SPS Palapa Saiyo Kecamatan Aur Birugo Tigo Baleh - Natsir, MHD; Hadi, Imanda Agustina (Jurnal Family Education, 2024)
This research was motivated by the low moral development of early childhood at SPS Palapa Saiyo, Aur Birugo Tigo Baleh District. This research aims to describe interpersonal communication in the family, the moral development of early childhood, and the relationship between interpersonal communication in the family and the moral development of children at SPS Palapa Saiyo, Aur Birugo Tigo Baleh District. The approach in this research was carried out quantitatively with a correlational type. The population at the research location was 26 subjects (children) represented by 52 parents (fathers and mothers). The sample was 70% of the total population namely, 18 children represented by 36 parents (fathers and mothers), with a sampling technique called Proportional random sampling. The data collection instrument used a questionnaire. The analysis technique used a percentage formula, and to find the correlation used the product moment formula. The results of this study show that: (1) Interpersonal communication between parents in the family and children is considered less than good. (2) Early childhood moral development is categorized as low, (3) There is a significant relationship between interpersonal communication in the family and children's moral development at SPS Palapa Saiyo, Aur Birugo Tigo Baleh District